Electrically treated composite FILMS based on chitosan and methylcellulose blends - Garcia, Maria Alejandra (2009)
Films obtained from chitosan (CH) and methylcellulose (MC) can reduce environmental problems associated with synthetic packaging. The objective of the present work was to analyze the effect of an electrical field applied during drying on microstructure and macroscopic properties of films obtained with different mixtures of CH and MC. SEM and X-ray diffraction indicated that CH electrically treated film exhibited a more ordered structure and lower water vapor permeability (WVP) values than those of the control films. With regard to mechanical properties of electrical treated samples, longitudinal probes presented higher elongation values than those of transverse ones. CH treated films showed higher Young's modulus values than the control ones; in composite control samples, Young's modulus and tensile strength increased with CH concentration, leading to stronger films. Electrical field treatment would be a good alternative to improve film flexibility and water vapor barrier properties.